2014
DOI: 10.1139/cjfas-2013-0381
|View full text |Cite
|
Sign up to set email alerts
|

Daytime avoidance of chemosensory alarm cues by adult sea lamprey (Petromyzon marinus)

Abstract: Sea lamprey (Petromyzon marinus) avoid damage-released and predator chemosensory cues at night, but their response to these cues during the day is unknown. Here, we explored (i) whether sea lamprey avoid these cues during the day and (ii) the effect of water temperature on the avoidance of chemosensory alarm cues in two diurnal laboratory experiments. We hypothesized that daytime activity would be temperature-dependent and that only sea lamprey vulnerable to predation (i.e., not hiding) would behaviourally res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 23 publications
2
17
1
Order By: Relevance
“…Pacific Lampreys may detect and avoid White Sturgeon using chemosensory cues, as many lamprey species have highly developed olfactory systems (Yun et al 2011). Several recent studies have shown Pacific Lamprey aversion to odors associated with predators and with lamprey injury and mortality (e.g., Imre et al 2010;Wagner et al 2011;Di Rocco et al 2014). Further studies are needed to verify that Pacific Lampreys respond to the presence of White Sturgeon, to identify the sensory mechanism employed (i.e., chemical, vibrational, visual), and to quantify the behavioral and survival effects of White Sturgeon on upstream passage through fishways.…”
Section: Discussionmentioning
confidence: 99%
“…Pacific Lampreys may detect and avoid White Sturgeon using chemosensory cues, as many lamprey species have highly developed olfactory systems (Yun et al 2011). Several recent studies have shown Pacific Lamprey aversion to odors associated with predators and with lamprey injury and mortality (e.g., Imre et al 2010;Wagner et al 2011;Di Rocco et al 2014). Further studies are needed to verify that Pacific Lampreys respond to the presence of White Sturgeon, to identify the sensory mechanism employed (i.e., chemical, vibrational, visual), and to quantify the behavioral and survival effects of White Sturgeon on upstream passage through fishways.…”
Section: Discussionmentioning
confidence: 99%
“…When the ammocoete arrived at the front end of the experimental arena and was exposed to PEa HCl, it rapidly changed direction, swimming quickly to the opposite end of the arena and vigorously burrowing into the substrate. this behaviour suggests that ammocoetes do respond to PEa HCl, not unlike migratory Sea Lampreys (imre et al 2014;Di Rocco et al 2014), but the alarm cues in our experiment did not seem sufficient to initiate relocation once ammocoetes were established in burrows. vulnerability to predation at this stage in life apparently prevented the ammocoetes from leaving the safety of an established burrow.…”
Section: Discussionmentioning
confidence: 51%
“…a push-pull strategy for Sea Lamprey control has been recently suggested by imre et al (2010), in which sex pheromones combined with chemosensory alarm cues would function to manipulate the behaviour of migratory Sea Lampreys by pushing them away from spawning habitats and luring them into areas where traps or other forms of control are deployed. Recent studies have demonstrated that migratory Sea Lampreys strongly avoid conspecific damage-released alarm and predator cues (Di Rocco et al 2014;.…”
Section: Introductionmentioning
confidence: 99%
“…We captured a single fish using a dip net, scanned for a PIT-tag code, and then transferred the fish to one of two randomly assigned mazes and tested over two consecutive nights. We placed each fish into its maze during the daytime, typically from 1000 hours to 1400 hours, and the antennas were turned on at this time; however, we did not expect searching activity to occur until sunset, as lamprey are not active during daytime hours (Robinson and Bayer 2005;Di Rocco et al 2014). Before the beginning of each experiment, we randomly determined which arm of the maze would receive the odor treatment (hereafter, treatment arm).…”
Section: Odor Experimentsmentioning
confidence: 99%
“…Strong responses to repellent odors could be used to influence the behavior of migrating fish. For example, manipulation of invasive sea lamprey in the Laurentian Great Lakes using odors has met with some success (Wagner et al 2011;Di Rocco et al 2014;Imre et al 2014;Hume et al 2015) and similar strong responses by Pacific lamprey could be an important management tool. Using odors to repel Pacific lamprey from locations at dams that hinder successful passage while guiding them with attractants toward installed lamprey passage structures is one example of their use as a management tool.…”
Section: Introductionmentioning
confidence: 99%